Increasing The Role of Rail-Based Public Transportation to Reduce Congestion in Jakarta - Soemino Eko Saputro; Edi Abdurachman; Prasadja Ricardianto; Julison Arifin; Umar Gassing (Dinasti Publisher, 2024)
Problems that cause public transport less desirable because the rail network is still minimal, public transport services still need to be improved, full integration can not be realized and the development of Transit Oriented Development can not be implemented as a whole. This study was conducted to determine whether the service model and public policy were successful, therefore the study used variables namely; Perceived Quality; Trust; Passenger Satisfaction; Perceived Value; Passenger Preference; Passenger Loyalty, Behavior Intention to Purchase, and Transit Oriented Development as moderation. The data analysis methods in this study include Importance and Performance Analysis (IPA), and Structural Equation Model (SEM) with the help of the SMART PLS program. This study used a sample of 400 respondents. Based on the results of the analysis perceived quality, Passenger satisfaction, trust, and Passenger loyalty can have a positive and significant effect on behavior intention to purchase but perceived value does not have a significant effect, so the development of transit-oriented development can have a significant effect on loyalty and behavior intention to purchase. Important performance analysis to improve service performance, namely train travel without obstacles, high reliability, and integrated and single ticket system.